RAFT‐based synthesis and the gelation property of telechelic polymers that can immobilize biomacromolecules. Issue 8 (9th February 2017) - Kinoshita, Keita; Takami, Taku; Mori, Yuta; Uchida, Yusuke; Murakami, Yoshihiko
ABSTRACT: Telechelic polymers, macromolecules having two reactive end groups, can serve as building blocks for constructing polymers or polymeric materials that have complex architectures. Among the telechelic polymers, polymers bearing hydroxyl groups at two terminals have been used as components for preparation of functional materials. In the present study, RAFT polymerization of both N ‐acryloylmorphorin and N ‐succinimidyl acrylate by using a newly synthesized dithiobenzoate‐type chain transfer agent bearing hydroxyl groups at both terminals (HECPHD) was reported. After the acryloylation of the hydroxyl terminals of the obtained polymer, gelation was observed. Furthermore, the polymer could react with a protein via the conjugation of the succinimidyl esters‐containing polymers to the amino groups present on the protein surface. The results show that activated esters‐bearing polymers with hydroxyl groups at both terminals can be used as building blocks for constructing polymeric materials for an immobilization of biomacromolecules. © 2016 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2017, 55, 1356–1365 Abstract : RAFT polymerization of both N ‐acryloylmorphorin and N ‐succinimidyl acrylate by using a newly synthesized dithiobenzoate‐type chain transfer agent bearing hydroxyl groups at both terminals (HECPHD) was carried out. After the acryloylation of the hydroxyl terminals of the obtained polymer, gelation was observed. The results show that activated esters‐bearing polymers with hydroxyl groups at both terminals can be used as building blocks for constructing polymeric materials for an immobilization of biomacromolecules.